2016
DOI: 10.1097/fjc.0000000000000429
|View full text |Cite
|
Sign up to set email alerts
|

GSK-3β Inhibitor CHIR-99021 Promotes Proliferation Through Upregulating β-Catenin in Neonatal Atrial Human Cardiomyocytes

Abstract: These results indicate that GSK-3β inhibitor can promote human atrial cardiomyocyte proliferation. Although it remains to be determined whether the observations in atrial myocytes could be directly applicable to ventricular myocytes, the current findings imply that Wnt/β-catenin pathway may be a valuable pathway for manipulating endogenous human heart regeneration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(24 citation statements)
references
References 30 publications
2
21
1
Order By: Relevance
“…In our study, we demonstrated that CHIR99021 treatment exhibited the best potential for cardiac regeneration as it is not only more efficient in inducing cardioproliferation, it also does not interfere with the function of N-cadherin required for cell adhesion and cardiac electrophysiological activity [ 42 ]. Consistent with this, recent studies have demonstrated that CHIR99021 alone can promote cardiomyocyte proliferation in neonatal atrial human cardiomyocytes [ 43 ], emphasizing again the feasibility of using CHIR99021 as a potential drug that can endogenously repair injured cardiac tissue and promote cardiac regeneration. We found that CHIR99021 exhibits cytotoxic effects at a concentration of more than 1 μM, plausibly due to several reasons which were not uncovered in this study.…”
Section: Discussionmentioning
confidence: 59%
“…In our study, we demonstrated that CHIR99021 treatment exhibited the best potential for cardiac regeneration as it is not only more efficient in inducing cardioproliferation, it also does not interfere with the function of N-cadherin required for cell adhesion and cardiac electrophysiological activity [ 42 ]. Consistent with this, recent studies have demonstrated that CHIR99021 alone can promote cardiomyocyte proliferation in neonatal atrial human cardiomyocytes [ 43 ], emphasizing again the feasibility of using CHIR99021 as a potential drug that can endogenously repair injured cardiac tissue and promote cardiac regeneration. We found that CHIR99021 exhibits cytotoxic effects at a concentration of more than 1 μM, plausibly due to several reasons which were not uncovered in this study.…”
Section: Discussionmentioning
confidence: 59%
“…Addition of CHIR99021 results in robust proliferation of mouse and human PSC-derived cardiomyocytes ( Figure 2 ), consistent with the essential roles of the Wnt/β-catenin pathway for ventricular cardiomyocyte proliferation during embryonic development ( Klaus et al, 2012 ; Buikema et al, 2013 , 2020 ). In addition, Wnt signaling-induced cardiomyocyte proliferation is also observed in human neonatal cardiomyocytes and mouse adult cardiomyocytes ( Wang et al, 2016 ; Fan et al, 2018 ). As NOTCH and Hippo pathways control cardiomyocyte proliferation through regulating Wnt/β-catenin pathway, manipulation of these pathway activities could boost the proliferation of early human iPSC-CMs to generate clinical-level magnitude for repairing the damaged myocardium.…”
Section: Harness Human Ipsc-derived Cardiomyocytes For Heart Regeneramentioning
confidence: 97%
“…These results were confirmed by Kim et al (2016), who showed that BIO not only induced BrdU incorporation in cultured neonatal rat CMs but also reduced BrdU incorporation in rat neonatal cardiac fibroblasts. Increased proliferation was also observed in cultured human atrial CMs treated with the GSK3-b inhibitor CHIR99021, albeit that the increase in proliferating CMs was modest (control: 1.83% 6 0.01%; CHIR: 2.67% 6 0.08%); in this study, inhibition of WNT/b-catenin signaling with 4-(1,3,3a,4,7,7a-hexahydro-1,3-dioxo-4,7-methano-2H-isoindol-2-yl)-N-8-quinolinyl-benzamide (IWR-1) resulted in a ∼35% reduction in CM proliferation (Wang et al, 2016). Adenoviral-mediated overexpression of b-catenin in neonatal rat CM, however, showed an initiation of the cell cycle; this did not result in an increased number of CMs but augmented CM hypertrophy and the number of binucleated cells (Hahn et al, 2006).…”
Section: Wnt Signalingmentioning
confidence: 56%